Calcareous nannofossil assemblages of the upper Miocene to Pliocene Shimajiri Group on Okinawa-jima, Ryukyu Islands, southwestern Japan. (March 2017) - Imai, Ryo; Sato, Tokiyuki; Iryu, Yasufumi
Highlights: High-resolution calcareous nannofossil biostratigraphy of the Shimajiri Group. Eutrophication was caused by shallowing of the sedimentary basin. Eutrophication occurred in the northwestern Pacific Ocean at 5 Ma. Abstract: We investigated the calcareous nannofossil biostratigraphy and paleoceanography of the Shimajiri Group in two exploratory wells (depths, 1243 and 1800 m) drilled on southern Okinawa-jima, Ryukyu Islands, southwestern Japan. Three late Miocene to Pliocene datum planes were identified: the first occurrence of Amaurolithus spp. (7.42 Ma), the last occurrence of Discoaster quinqueramus (5.59 Ma), and the first occurrence of Ceratolithus rugosus (5.12 Ma). These datum planes were also identified in two other deep wells on southern Okinawa-jima. Nutrient levels (reconstructed from the relative abundances of small Reticulofenestra spp., and the relative abundances of Discoaster spp. plus Sphenolithus abies ) suggest that deposition of the Shimajiri Group (<8.29–3.50 Ma) occurred under conditions of increasing eutrophication. The eutrophication was likely caused by shallowing of the sedimentary basin, but a stepwise shift was associated with an abrupt eutrophication event that occurred in the northwestern Pacific Ocean at 5 Ma.